2014
DOI: 10.1111/jir.12140
|View full text |Cite
|
Sign up to set email alerts
|

Medical, psychological and social features in a large cohort of adults with Prader–Willi syndrome: experience from a dedicated centre in France

Abstract: Adult patients with PWS showed high prevalence of comorbid health problems that need to be monitored for early treatment. Some of them are influenced by genotype and age. Another salient problem concerns the lack of adapted structures for better social integration. Further data about the real life and health conditions of adults with PWS are necessary to further our knowledge of the natural history of the disease and to design appropriate care strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 29 publications
11
55
1
1
Order By: Relevance
“…In one cohort data in UK, the mean age of onset was 20 years and the prevalence was around 25% (16/66) 10) . A large population-based adult cohort study in France has shown similar results such as 25% of T2DM prevalence and mean onset of age of 24 years 11) . Otherwise, in one cohort of 83 PWS patient in South Korea (Samsung Medical center) , the prevalence of PWS with T2DM was reported as 32.5%, which was higher than in other European countries, while the mean onset of age, 21.4 years-old, was shown similar finding with others country (unpublished data, 2015 year).…”
Section: Epidemiology Of Diabetes In Pwssupporting
confidence: 50%
“…In one cohort data in UK, the mean age of onset was 20 years and the prevalence was around 25% (16/66) 10) . A large population-based adult cohort study in France has shown similar results such as 25% of T2DM prevalence and mean onset of age of 24 years 11) . Otherwise, in one cohort of 83 PWS patient in South Korea (Samsung Medical center) , the prevalence of PWS with T2DM was reported as 32.5%, which was higher than in other European countries, while the mean onset of age, 21.4 years-old, was shown similar finding with others country (unpublished data, 2015 year).…”
Section: Epidemiology Of Diabetes In Pwssupporting
confidence: 50%
“…<25%; Cans et al, 1999) of those with intellectual disabilities requiring postural care will have cerebral palsy. Indeed, a number of specific conditions related to intellectual disabilities may result in the need for postural care (Ager et al, 2006;Burns, Powell, Hsia, & Reinker, 2003;Butler et al, 2002;Damasceno, Cristante, Marcon, & Barros Filho, 2014;Detweiler, Thacker, Hopkins, Conway, & Gripp, 2013;Imagama et al, 2013;Karmaniolou, Krishnan, Galtrey, Cleland, & Vijayaraghavan, 2015;Kerr, Webb, Prescott, & Milne, 2003;Laurier et al, 2015;Li, Shen, Liang, & Sheng, 2015;de Lind van Wijngaarden, de Klerk, Festen, & Hokken-Koelega, 2008;Takebayashi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, it may also be hypothesised that some individuals outside of the patient association are coping well and thus do not necessarily feel the need to be involved with a patient association. However, the characteristics of our population in terms of age and treatments received (invasive ventilation, GH or other endocrine treatments or psychotropic drugs) are close to those of the population suffering from PWS hospitalised in a dedicated centre in France (Laurier et al 2015).…”
Section: Discussionmentioning
confidence: 85%
“…However, the characteristics of our population in terms of age and treatments received (invasive ventilation, GH or other endocrine treatments or psychotropic drugs) are close to those of the population suffering from PWS hospitalised in a dedicated centre in France (Laurier et al . ).…”
Section: Discussionmentioning
confidence: 97%